Distingsi Kewenangan Eksekutorial Bank dan Sita Jaminan Pengadilan dalam Perspektif Keadilan Hukum - Seja Riyandani; Elfa Murdiana; Rafi Nailul Huda, M; Fikri Haikal; Della Marchellina S (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study examines the distinction between banks' executorial authority and the judicial authority of courts in imposing conservatoir beslag within Islamic banking disputes, while reconstructing the conceptual boundaries of these authorities from the perspective of legal justice. Employing a qualitative field research design with a socio-legal approach, the study integrates empirical legal research with normative legal analysis. Primary data were obtained from Decision of the Tanjung Karang Religious Court No. 7/Pdt.G.S/2025/PA.Tnk and in-depth interviews with judges of the Religious Court, whereas secondary data consisted of statutory regulations, court decisions, scholarly books, and reputable journal articles. The findings reveal that banks' executorial authority and the judicial authority to impose conservatoir beslag belong to distinct legal regimes and therefore should not be conflated. Rejecting an application for conservatoir beslag solely on the basis of the bank's executorial rights may undermine the preventive function of judicial attachment and weaken the quality of judicial reasoning. This study proposes a reconstructed framework that positions both authorities as complementary legal mechanisms, thereby strengthening legal certainty, procedural justice, and judicial accountability in the resolution of Islamic banking disputes.